Unusual in Growth and Composition: Ethiopian Private Higher Education - Tamrat, Wondwosen; Levy, Daniel (International Higher Education, 2017)
Ethiopia’s private higher education (PHE) sector is the largest or second largest in sub-Saharan Africa, however a mix of enabling and restrictive policies have let PHE play a limited role in key respects. This article surveys the current landscape and asks important questions regarding the future of PHE.